Study of the Most Important Factors of Real Estate Valuation Affecting the Real Estate Market (Case Study Jableh City) (Latakia University Journal -Engineering Sciences Series, 2020)
He subject of correct and accurate real estate valuation is the safety factor in the work of real estate banks or real estate investment bodies and plays a key role in maintaining the balance of the real estate market in different countries. Real estate valuation is a systematic process aimed at calculating the actual value of the property at a specific time by studying its various engineering, legal and environmental characteristics as well as the economic factors affecting it. This topic has been subject to the experience of real estate residents without clear scientific controls for a long period of time. Recent decades around the world have been characterized by a dramatic increase in the number of real estate investments with the increasing number of clients of these investments and the emergence of cross-border partnerships between lenders, and the increase in data accompanying real estate investment operations with emphasis on the sensitivity of these Data and its close association with the rights of depositors and investors All this demonstrated the need to establish scientific controls for the real estate valuation process, taking advantage of the technological advances taking place globally, especially in the field of spatial data management. In Syria, the real estate valuation process continues to be a collection of experience often inherited from the real estate developer and is subject to many fluctuations, the most important of which is the degree of responsibility and integrity enjoyed by an experienced real estate resident. The study aims to develop a scientific methodology suitable for the real estate valuation process starting with identifying the factors affecting the rise or decline of the value of real estate and studying the severity of the impact of these factors on the value of real estate in a region or city. With a wide range of real estate valuation factors, it allows them to be studied and their relative importance well determined. يعتبر موضوع التقييم العقاري الصحيح والدقيق عامل الأمان في عمل المصارف العقارية أو هيئات الاستثمار العقاري كما يلعب دوراً أساسياً في الحفاظ على توازن سوق العقارات في الدول المختلفة. يُعتبر التقييم العقاري عملية منهجية تهدف لحساب القيمة الفعلية للعقار في زمن محدد من خلال دراسته بمختلف خصائصه الهندسية، القانونية، البيئية إضافة إلى دراسة العوامل الاقتصادية المؤثرة. ظل هذا الموضوع مرتهناً بخبرة المقيمين العقاريين دون ضوابط علمية واضحة لفترة طويلة من الزمن. تميزت العقود الأخيرة على مستوى العالم بالتزايد الهائل لحجوم الاستثمارات العقارية مع ازدياد أعداد المتعاملين بهذه الاستثمارات وظهور الشراكات العابرة للحدود بين الهيئات المقرضة، وزيادة البيانات المرافقة لعمليات الاستثمار العقاري مع التأكيد على حساسية هذه البيانات وارتباطها الوثيق بحقوق المودعين والمستثمرين. كل هذا أظهر الحاجة إلى وضع ضوابط علمية لعملية التقييم العقاري مستفيدين من التقدم التكنولوجي الحاصل عالمياً وخصوصاً في مجال إدارة البيانات المكانية. في سورية لا تزال عملية التقييم العقاري محصّلة لخبرة موروثة في غالب الأحيان للمقيم العقاري وهي تخضع لتقلبات كثيرة أهمها درجة الإحساس بالمسؤولية والنزاهة اللذان يتمتع بهما المقيم العقاري الخبير. تهدف الدراسة إلى وضع منهجية علمية مناسبة لعملية التقييم العقاري بدءاً بتحديد العوامل المؤثرة في ارتفاع أو انخفاض قيمة العقار ودراسة شدة تأثير هذه العوامل على قيمة العقارات في منطقة أو مدينة ما.تم اختيار مدينة جبلة في محافظة اللاذقية كمنطقة دراسة حيث تتميز هذه المدينة بتوافر شريحة واسعة لعوامل التقييم العقاري مما يتيح دراستها وتحديد أهميتها النسبية بشكل جيد.